A faith not worth fighting for: addressing commonly asked questions about Christian nonviolence - York, Tripp; Barringer, Justin Bronson (The peaceable kingdom series, 2012)
Introduction: Why refusing to kill matters for Christian discipleship / Justin Bronson Barringer and Tripp York -- Isn't pacifism passive? / C. Rosalee Velloso Ewell -- What about the protection of third-party innocents? / D. Stephen Long -- What would you do if someone were attacking a loved one? / Amy Laura Hall and Kara Slade -- What about Hitler? / Robert Brimlow -- Must Christian pacifists reject police force? / Gerald W. Schlabach -- What about those men and women who gave up their lives so that you and I could be free? / Justin Bronson Barringer -- Does God expect nations to turn the other cheek? / Gregory A. Boyd -- What about war and violence in the Old Testament? / Ingrid E. Lilly -- What about Romans 13: "Let every soul be subject"? / Lee C. Camp -- Didn't Jesus say he came not to bring peace, but a sword? / Samuel Wells -- What about the centurion? / Andy Alexis-Baker -- Didn't Jesus overturn the tables and chase people out of the temple with a whip? / John Dear -- What about the warrior Jesus in Revelation 19? / J. Nelson Kraybill -- Conclusion: A faith worth dying for : a tradition of martyrs not heroes / Tripp York